Empowering Voices: The Unsung Role of Women in Establishing and Sustaining the Pelindaba Treaty for an African Nuclear Weapon–Free Zone - Heba Fathy Elkomey; Alejandra Loreto Alfaro; Dennis Balami; Adeline Yuego; miriam Yartey; Geraldine Okoye (International Journal of Nuclear Security, 2025)
The Pelindaba Treaty, officially known as the African Nuclear-Weapon-Free Zone (NWFZ) Treaty, stands as proof of Africa’s collective commitment to a nuclear-weapon-free continent. It was opened for signature in 1996 in Cairo, Egypt, and entered into force in 2009. Its main aim is to prevent the development, acquisition, possession, or stationing of nuclear weapons within the zone, thereby promoting peace and security for all African nations. The treaty outlines an array of comprehensive measures to achieve this goal. State parties are prohibited from engaging in any nuclear weapon–related activities. Also, the treaty requires parties to maintain the highest standards of physical protection of nuclear materials, facilities, and equipment to prevent theft or unauthorized use and handling. Additionally, the treaty requires parties to concurrently achieve the highest standards of physical protection of nuclear material, which can be used for peaceful purposes. According to the United Nations (UN), 51 of the 55 African states have signed the Pelindaba Treaty, and 43 of them are parties to the treaty. Although the treaty is rightfully viewed as a monumental diplomatic achievement, the indispensable groundwork and ongoing stewardship by African women activists and policymakers that enabled its success often remains overlooked. This paper illuminates the bold vision and vital contributions of female diplomats, protest organizers, and governance leaders in actualizing and faithfully upholding the Pelindaba Treaty over the past three decades by review women’s involvement in African peace and security organizations operating. Additionally, this work highlights women’s contribution to disarmament efforts and their engagement’s effect in the NWFZ, sustaining and enforcing the Pelindaba Treaty within their positions of influence. The paper profiles pioneering negotiators such as Dr. Nkosazana Dlamini-Zuma, former chairperson of the African Union Commission, known as the depositary of the African NWFZ Treaty, noting her role in overseeing the treaty's implementation and compliance. On the diplomatic front is Nigeria’s Ambassador Joy Ogwu, whose wise leadership guided the treaty from conception to ratification, building consensus across diverse African interests.
Keywords: Pelindaba Treaty; Africa; Women; Nuclear Security; Non-proliferation